Pengaruh Prāṇāyāma Terhadap Peningkatan Kapasitas Vital Paru Pada Remaja Di Santi Srama Bulaki Studio Yoga - Putri Ramuja Dewi Sugata; I Made Sugata; Putu Emy Suryanti (Jurnal Yoga dan Kesehatan, 2023)
A lifestyle that tends to be positive and healthy will have a better quality. One of the organs of the body that is very influential when a person's lifestyle is unhealthy is the part of a person's lungs. The lung organ has an ability that is supported by two factors in it, namely the volume of oxygen that will enter the body and of course another one in the vital capacity of the lungs to accommodate this oxygen. One of the factors that can influence the increase in lung vital capacity is prāṇāyāma practice. Prāṇāyāma is a regulation of good breath in and out of the lungs through the nostrils with the aim of spreading Prana (energy) to all parts of the body and increasing the vital capacity of the lungs. This prāṇāyāma practice technique can be practiced at Santi Srama Bulaki Yoga Studio. The research method used is quantitative with a research design "One group pre-test-post-test Design", with a total sampling technique. The samples in this study were 17 young women aged 14-24 years who had met the inclusion and exclusion criteria. Data collection methods used were observation, interviews, and measurements (Spirometric measuring instrument). The collected data was analyzed using the IBM SPSS Statistics 21 for Windows application with a statistical test, namely the Wilcoxon Signed Ranks Test. The output statistical test results of the Wilcoxon Signed Ranks Test obtained an Asymp.Sig.(2-Tailed) value of 0.000. This value of 0.000 indicates that 0.000 < 0.05. This shows and proves that the hypothesis Ha is accepted and Ho is rejected, which means that there is an influence of prāṇāyāma on increasing lung vital capacity in adolescents at Santi Srama Bulaki Yoga Studio. So the conclusion is that Prāṇāyāma has an effect on increasing the vital capacity of the lungs.